Psychological Background of Age Differences in the Adaptation of Ukrainian Winterers to Living Conditions in Antarctica - Olena A. Miroshnychenko (Mukachevo State University, 2021)
The relevance of the article stems from the fact that every year for 26 years, the expedition of winterers goes to the Ukrainian Antarctic Station "Vernadsky Research Base" to carry out scientific research. Their effective adaptation to extreme conditions of life provides qualitative psychological diagnostics and psychological recommendations. The purpose of this article is to provide a theoretical justification and empirical evidence of the specific features of Ukrainian winterers' age in the process of adaptation to the Antarctica conditions. To achieve the results of the study, the article uses the method of sociometric measurement J. Moreno, method of distributing topics by rank, questionnaire. The authors of the article analysed scientific works on the research problem, clarified the concept of "adaptation" and "adaptability" and age limits of the groups of winterers, described methodological tools and conducted empirical research on the specific features of the age of winterers groups during the adaptation. The article justifies the distribution and identifies groups of high, medium and low adaptability to life under extreme conditions in Antarctica. The authors analysed both the data from the empirical study and the interviews with the surveyed winterers. The study's conclusions are: senior winterers have more experience adapting to extreme conditions than younger generations. They can build better interpersonal relationships in a closed community and easily carry distance from home and homesickness. The study revealed that senior persons (especially representatives of the "Generation of winners' children") motivate wintering in Antarctica with a desire for self-fulfilment, being worthy representatives of Ukraine on a distant continent, and feeling responsible for discharging their duties. After all, they are governed by more professional and social motivations that help to better adapt to extreme conditions. The practical value of the work is to develop tools for psychological diagnosis and to provide guidance on the selection of winterers among candidates for wintering